2018
DOI: 10.1007/s00213-018-5072-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intra-accumbal or intra-prefrontal cortex microinjections of adenosine 2A receptor ligands on responses to cocaine reward and seeking in rats

Abstract: Rationale and objectivesMany studies indicated that adenosine via its A2A receptors influences the behavioral effects of cocaine by modulating dopamine neurotransmission. The hypothesis was tested that A2A receptors in the nucleus accumbens (NAc) or the prefrontral cortex (PFc) may modulate cocaine reward and/or cocaine seeking behavior in rats.MethodsThe effects of local bilateral microinjections of the selective A2A receptor agonist CGS 21680 or the A2A receptor antagonists KW 6002 and SCH 58261 were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 70 publications
(123 reference statements)
0
14
0
Order By: Relevance
“…The latter authors found also that none of the CGS 21680 effective doses changed the inactive lever responses, which indicated the drug specificity. Wydra and colleagues [ 92 ] also pointed to the important role of the localization of A 2A Rs in controlling the rewarding effects of cocaine. Namely, in the intra-accumbal shell, but not the intra-infralimbic prefrontal cortex, microinjections of CGS 21680 (1.0–2.5 ng/side) dose-dependently decreased cocaine (0.25 mg/kg/infusion) self-administration.…”
Section: A 2a R and Behavioral Actions To Cocaimentioning
confidence: 99%
See 4 more Smart Citations
“…The latter authors found also that none of the CGS 21680 effective doses changed the inactive lever responses, which indicated the drug specificity. Wydra and colleagues [ 92 ] also pointed to the important role of the localization of A 2A Rs in controlling the rewarding effects of cocaine. Namely, in the intra-accumbal shell, but not the intra-infralimbic prefrontal cortex, microinjections of CGS 21680 (1.0–2.5 ng/side) dose-dependently decreased cocaine (0.25 mg/kg/infusion) self-administration.…”
Section: A 2a R and Behavioral Actions To Cocaimentioning
confidence: 99%
“…If pharmacological stimulation of A 2A Rs attenuated the drug reward, the tonic activation of these receptors with selective antagonists seemednot to be linked to drug motivational or reinforcing effects. Thus, neither systemic administration of MSX-3 (3.0 mg/kg) nor systemic or local (into the nucleus accumbens or prefrontal cortex) microinjections of KW 6002 (1.0–2.5 μg/side) or SCH 58261 (1.0–2.5 µg/side) altered cocaine self-administration in squirrel monkeys [ 96 ] or rats [ 92 ].…”
Section: A 2a R and Behavioral Actions To Cocaimentioning
confidence: 99%
See 3 more Smart Citations